2010
DOI: 10.1590/s1516-18462010005000064
|View full text |Cite
|
Sign up to set email alerts
|

Potenciais evocados auditivos por frequência específica em lactentes com audição normal

Abstract: RESUMOObjetivo: determinar os níveis mínimos de resposta (NMR) e a latência da onda V em lactentes ouvintes nas frequências de 0.5, 1, 2 e 4 kHz. Método: foram avaliados 23 lactentes sem indicadores de risco para deficiência auditiva que apresentavam emissões otoacústicas evocadas por estímulo transiente (EOAET) e potenciais evocados auditivos de tronco encefálico automático (PEATE-A) presentes bilateralmente. Resultados: obtiveram-se NMR médios de 34.2 dBnNA, 25.4 dBnNA, 19 dBnNA e 17.5 dBnNA para as frequênc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
2
12

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 13 publications
6
12
2
12
Order By: Relevance
“…This finding corroborate several studies 14,[16][17][18][19][20] , in which the mean MRL were different from the present study by less than 10 dB. A meta-analysis and a study conducted in 2007 both showed lower MRL -19.6 and 18.4 dBnHL, respectively 11,21 .…”
Section: Presence Of Wave Vsupporting
confidence: 90%
See 4 more Smart Citations
“…This finding corroborate several studies 14,[16][17][18][19][20] , in which the mean MRL were different from the present study by less than 10 dB. A meta-analysis and a study conducted in 2007 both showed lower MRL -19.6 and 18.4 dBnHL, respectively 11,21 .…”
Section: Presence Of Wave Vsupporting
confidence: 90%
“…Air conduction Regarding the function latency X intensity, a latency increase was observed with the decrease of the intensity level used to trigger the response, as well as a latency decrease with the increase of the frequency assessed, as suggested in the literature 18,20,31 . In the present study, the function latency X intensity in the frequencies of 500 and 1000 Hz did not behave as shown in literature 18,20,31 , since these frequencies were very similar at the intensities of 80 and 60 dBnHL.…”
Section: Function Latency X Intensitymentioning
confidence: 54%
See 3 more Smart Citations